STUDENTS’ REFLECTION TOWARD LEARNING VOCABULARY USING DUOLINGO APPLICATION - Retno Wiyati; Shakilatasya Amelia (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2022)
Vocabulary plays an essential role for the students in acquiring a language because it is used to express thoughts, ideas, and information. However, due to its broad materials and time limit provided by the school, vocabulary cannot be studied optimally. As for it, the students should be more aware to learn the vocabulary independently, for example by utilizing the use of online language learning application, such as Duolingo. Therefore, this research is conducted to investigate the students’ reflection regarding their vocabulary learning using Duolingo Application. The participants of this research are three junior high school students in Cimahi, because the students meet the Duolingo’s curriculum target. The method of the research is a case study design. To acquire the data needed in this study the instruments used are interview and observation. From all the data obtained, researcher finally concludes that the students reflect positive attitudes toward the Duolingo application due to its advanced features. The students become more challenged to play the application and feel less worry because Duolingo provides them with many immediate feedbacks, well-structured materials and appreciation tags which can ease, motivate and reassure the students to achieve their learning goals. Nevertheless, the students face some drawbacks, such as the unnatural sentences, repeated questions, and lack of grammar guide. Even though, the students use the third party to manage the problem emerged.